Appropriation of Digital Technology in Popular Education - Casano, Leyla (2022)
The purpose of this research is to give an account of the appropriation of digital technology by a group of economically vulnerable families, within the framework of a popular education experience, in a district of metropolitan Lima. The methodology used follows the qualitative approach, with case study design, and with exploratory scope. It is concluded that, with adequate planning and strategies, digital appropriation is possible and its results are encouraging; however, the technological limitations of the social segment require constantly updating the process and even resorting to a combination of physical and digital components.